2021
DOI: 10.1002/adem.202100326
|View full text |Cite
|
Sign up to set email alerts
|

Adjusting Sensitivity and Linearity of the Wearable Pressure Sensors by an Arbitrary Micro‐Protuberance Structure of Polyvinylidene Fluoride/Reduced Graphene Oxide Dielectric Films

Abstract: Flexible pressure sensors with high sensitivity over a broad linear range and fast response have extension applications in wearable electronics. Herein, we prepared a tunable capacitive pressure sensors based on arbitrary micro‐protuberances geometry films via low‐cost soft lithography, employing the polyvinylidene fluoride/reduced graphene oxide (PVDF/rGO) composite with a high dielectric constant of 172 and low loss tangent of 0.48. The hierarchical microstructures’ different sizes endow the sensors adjustab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 32 publications
(45 reference statements)
0
4
0
Order By: Relevance
“…The hierarchical microstructure of PVDF/rGO dielectric film was prepared by low‐cost soft lithography, as reported in our work. [ 30 ] Specifically, the microstructured PDMS templates were fabricated by commercial sandpaper with various granularities (marked as 150 Cw, 400 Cw, 800 Cw, 1200 Cw, and 2000 Cw). Subsequently, the PVDF/rGO dielectric films with hierarchical microstructure were obtained using the as‐prepared PDMS templates, which is described as follows: First, graphene oxide (GO) powder (Chongqing Mohi Technology Co., Ltd., average particles size <45 μm; purity >99%) was dispersed in a 10 mL of dimethylformamide (Guoyao Group Chem.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The hierarchical microstructure of PVDF/rGO dielectric film was prepared by low‐cost soft lithography, as reported in our work. [ 30 ] Specifically, the microstructured PDMS templates were fabricated by commercial sandpaper with various granularities (marked as 150 Cw, 400 Cw, 800 Cw, 1200 Cw, and 2000 Cw). Subsequently, the PVDF/rGO dielectric films with hierarchical microstructure were obtained using the as‐prepared PDMS templates, which is described as follows: First, graphene oxide (GO) powder (Chongqing Mohi Technology Co., Ltd., average particles size <45 μm; purity >99%) was dispersed in a 10 mL of dimethylformamide (Guoyao Group Chem.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the permittivity performance of PVDF/reduced graphene oxide (PVDF/rGO) composite films has been system studied in our previous work. [ 30 ] Herein, we reported a flexible CPS based on PVDF/rGO films with multilayer and hierarchical microstructures (150/400/800 CW films‐3L) composed of irregular protrusions and the successive roughness (remarked as 150 Cw, 400 Cw, 800 Cw). Due to the synergistic effect of the structural compressibility and effective stress distribution of stacked multilayers under pressure, the sensor has a good sensitivity (0.18 kPa −1 ) in a wide linear range of 0.1 kPa–11 kPa, and is not easy to be saturated in the high‐pressure range of 360 kPa.…”
Section: Introductionmentioning
confidence: 99%
“…The passive design of irregular microstructures with multiscale hierarchical properties offers an optimal solution for realizing continuous deformation with pressure 20,21 . Previously, methods of inverting naturally occurring microstructural templates (e.g., pollen grains 22 or petals 23 , human skin 24,25 , abrasive paper 26 , and kirigami patterns 27 ) or MEMS-fabricated artificial patterns [28][29][30][31] have been introduced for piezoresistive sensors to fabricate active layers. For example, Geng et al reported an ordered multilevel microstructure and explored the regulations of its radius and spatial distribution impacting the sensor performance merely via simulations and experiments 32 , rather than from a quantitative perspective.…”
Section: Introductionmentioning
confidence: 99%
“…The advantages of using capacitive pressure sensors are notable. Firstly, they exhibit low energy consumption, making them suitable for battery-operated devices and applications where power efficiency is critical [22]. Secondly, capacitive sensors offer high repeatability, ensuring consistent and reliable measurements over time [23].…”
Section: Introductionmentioning
confidence: 99%